Toward pH independent oxygen reduction reaction by polydopamine derived 3D interconnected, iron carbide embedded graphitic carbon - Gangadharan, Pranav K.; Pandikassala, Ajmal; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2021)
Recent advancements on the development of nonprecious electrocatalysts with iron (Fe) incorporated active centers have generated confidence on realizing cost-effective proton exchange membrane fuel cells (PEMFCs). However, most of these catalysts that emerged as a substitution for the platinum supported on carbon (Pt/C) catalysts in oxygen reduction reaction (ORR) are active under basic conditions, and their feasibility in PEMFCs remains as a challenge. In this scenario, this work reports the synthesis of a Pt-free oxygen reduction electrocatalyst prepared by the annealing of polydopamine grown melamine foam. The prepared catalyst has a three-dimensional (3D) interconnected bilayer network structure possessing the carbon nitride backbone wrapped by graphitic carbon layer bearing iron carbides and nitrides as the active centers (3DFePDC). Interestingly, the 3D-FePDC catalyst displayed an ORR activity both under acidic and basic conditions. Whereas the ORR performance of 3D-FePDC closely matches that of the commercial Pt/C in the basic medium, it displays only a low overpotential value of 60 mV under acidic conditions compared to its Pt counterpart. The kinetics of ORR on 3DFePDC is found to be similar to the four-electron (4e) reduction pathway displayed by Pt/C. Testing of a PEMFC in a single cell mode by using 3D-FePDC as the cathode catalyst and Nafion membrane delivered a maximum power density of 278 mW cm(-2), which is a promising value expected from a system based on the nonprecious metal cathode. Ultimately, as a cost-effective catalyst that can effectively perform irrespective of the pH conditions, 3D-FePDC offers significant prospects in the areas like fuel cells and metal-air batteries which work in acidic and/or basic conditions.
Keywords: acidic medium; electrocatalyst; fuel cell; graphitic carbon; Iron carbide; nitrogen doping; nonprecious metal; oxygen reduction reaction

Tuning of oxygen reduction pathways through structural variation in transition metal-doped Ba2In2O5 - Thundiyil, Shibin; Pandikassala, Ajmal; Kurungot, Sreekumar; Devi, R. Nandini (ChemElectroChem, 2022)
Abstract Oxygen reduction reaction (ORR) can take place either through a two-electron pathway to form H2O2 or through a four-electron pathway to form H2O. Both the reactions are important in the respective fields, viz., H2O2 production as well as fuel cell technology, and rational design of catalysts is mandatory to acquire high energy efficiency in both cases. Here, we report the structure-electrochemical property correlation of a series of perovskite related brownmillerite compounds, Ba2In0.75M0.25O5 (M=Mn/Fe/Co/Ni/Cu), synthesized by solid-state method. On transition metal doping, octahedral distortions were observed, and the highly disordered material tends to follow the 4e transfer mechanism. More symmetrical structures followed the 2e pathway to form H2O2 as the product with high peroxide selectivity. The distortion in the octahedral arrangement can be a descriptor to finetune the selectivity of the catalysts towards the 2e and 4e pathways of ORR.
Keywords: brownmillerite; Descriptors; Electrochemical H2O2 synthesis; Octahedral distortion; oxygen reduction reaction